The effectiveness of providing turmeric and tamarind herbal drink on reducing menstrual pain scale in students - Irawati Irawati; Mardiana Mardiana (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Menstrual pain, or dysmenorrhea, is a common complaint among women of reproductive age, particularly adolescents and young adults. This condition is characterized by cramps or pain in the lower abdomen that can radiate to the waist and thighs and generally occurs before or during menstruation. One popular approach is the use of herbal plants, in line with increasing public awareness of a healthy lifestyle and the use of natural ingredients. Purpose: To determine the effectiveness of turmeric and tamarind herbal drink on reducing menstrual pain and dysmenorrhea in D3 nursing students at the Batari Toja Bone Institute. Method: This study involved 20 female nursing students and used a quasi-experimental design. The study design was a pre-posttest one-group design, namely a design before and after the turmeric and tamarind drink intervention. The sampling technique used was purposive sampling. Analysis used univariate and bivariate analysis with paired simple t-tests. The results of the paired T-test, comparing menstrual pain experienced by respondents before and after the intervention, showed that the turmeric and tamarind drink had an effect on reducing primary menstrual pain, as indicated by a P-value of 0.0001, meaning <α 0.05. This resulted in the acceptance of Ha and the rejection of Ho, indicating that the turmeric and tamarind drink had an effect on reducing primary menstrual pain in female nursing students. Results: There was a decrease in the dysmenorrhea scale before and after the turmeric and tamarind administration. Before the turmeric and tamarind administration, most respondents were in the moderate pain category (11 respondents (55%), while after the turmeric and tamarind administration, most respondents were in the no pain category (7 respondents (35%). Conclusion: According to the researcher's assumption, the dysmenorrhea pain experienced by respondents before the turmeric and tamarind administration was caused by excessive production of the hormone prostaglandin during menstruation, which causes uterine muscle contractions and leads to primary dysmenorrhea.